A Systematic Literature Review of Science Process Skills in Indonesia: Analysis of Research Design and Data Analysis Methods (2015-2025) - Muhammad Zaini; Agus Ramdani; Ahmad Harjono; Muh. Makhrus; Aris Doyan; AA Sukarso (International Journal of Contextual Science Education, 2026)
Research on science process skills (SPS) in Indonesia has grown rapidly over the past decade; however, no comprehensive synthesis has yet been conducted on the research designs and data analysis techniques employed in these studies. This study aims to identify, evaluate, and synthesize SPS research in Indonesia from 2015 to 2025, with a specific focus on research designs and data analysis methods. The review followed the PRISMA 2020 guidelines. Literature searches were conducted in SciSpace (1,085 articles), Google Scholar (58 articles), and PubMed (0 articles) using keywords related to science process skills and Indonesia. After removing duplicates, 87 unique articles were screened based on title and abstract, yielding 20 articles for full-text assessment, of which 19 met the inclusion criteria and were analyzed in depth. Among these 19 studies, quasi-experimental designs predominated (n = 14; 73.7%), followed by pre-experimental designs (n = 3; 15.8%) and other designs, including development and descriptive studies (n = 2; 10.5%). The most frequently used data analysis methods were t-tests (n = 11; 57.9%), N-Gain (n = 8; 42.1%), and ANCOVA (n = 2; 10.5%). Most studies were conducted at the senior secondary (n = 9; 47.4%) and higher education levels (n = 3; 15.8%). Guided inquiry learning emerged as the most commonly investigated intervention, consistently yielding significant gains in students’ SPS. Overall, SPS research in Indonesia remains dominated by quasi-experimental, quantitatively oriented designs, indicating the need for greater diversification, including longitudinal, mixed-methods, and qualitative studies, along with standardization of SPS measurement instruments, improved methodological reporting, and exploration of more diverse learning contexts.